We don't need to agree to coordinate. - CAHILL, VINNY; BOUROCHE, MELANIE (IEEE, 2008)
Autonomous mobile entities are playing an ever increasing role in our everyday lives. When such entities operate in the same environment, they need to coordinate their behaviour in order to ensure system-wide safety constraints. As these entities are mobile, they can only communicate over wireless (possibly ad hoc) networks. In wireless networks, however, communication is unreliable, therefore consensus-based coordination cannot be applied. This means that entities need to take decisions independently, while having access to only limited information. This short paper describes an approach for entities to coordinate their behaviour without needing to reach a consensus. This approach is based on the notion of responsibility, which allows the duty of ensuring the safety constraints to be dis- tributed over entities. We dene the responsibility condition formally, and give an intuition as to how it can be used to by autonomous entities to coordinate their behaviour.
Michael Mock
PUBLISHED
Workshop on Dependable Network Computing and Mobile Systems (DNCMS'08)
Workshop associated with the 27th IEEE Symposium on Reliable Distributed Systems (SRDS 2008).
Keywords: Computer Science